Sacrílegas palavras: Inconfidência e presença jesuítica nas Minas Gerais durante o período pombalino - Leandro Pena Catao (2005)
This paperwork intendsto analyze four Inconfidences that happened in the locality of Minas Gerais during the government of Pombal. The Inconfidence of Curvelo, 1760-1763; the Inconfidence of Mariana, 1769; the the Inconfidence of Sabará, 1775 and, finally, another Inconfidence in Curvelo, 1776. In all of these events, the government and Dom Josés figure, such as the figure of his minister, Pombal, were hardly attacked, what characterized a crime of inconfidence. In that period, Pombal promoted several reforms with politic, social and economic nature in Portugal, what put the Portuguese State and The Society of Jesus in route of collision. The reason of these attacks to the monarch and his minister was the expulsion of the priests of The Society of Jesus of the Portuguese domain, as a result of wide those reforms promoted by Pombal, specially the submission of Church to the State. These Inconfidences also demonstrate the great influence that The Society of Jesus exercised above the vassals. Although the contrary dispositions of the Crown to the presence of regular priests in Minas, at that time, the Jesuits always been in this lands since the early colonization and even after the expulsion, another demonstration of the power of this Order. The Inconfidences show up conflicts of local sphere involving elites of Minas Gerais, confrontations involving regular priests in disputes for public positions and other advantages. It inaugurates a new model of politic contestation in Minas Gerais of 1770´s.